Paradoxes of the public school : historical and contemporary foundations of American public education - Schul, James E. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Revised thoroughly and updated, this second edition of Paradoxes of the Public School comprehensively explores public education in the United States. Researchers, faculty, and students will find this book accessible, insightful, and provocative. The book is packed with school history, theory, and data that are practically applied to a clear and fluid treatment of contemporary issues. Such issues include those related to areas such as religion, democratic citizenship, the teaching profession, race, academic freedom, social class, exceptionality, gender, technology, and privatization. Written with a clear and engaging prose, Paradoxes of the Public School is designed to be useful for both individuals seeking a first encounter to understand public education as well as longstanding education scholars"--